A real-world evaluation of a tertiary care childhood obesity intervention to reduce metabolic risk in a hard-to-reach urban population - Nagla S. Bayoumi; Elizabeth Helzner; Aimee Afable; Michael A. Joseph; Sarita Dhuper (BMC, 2019)
Abstract Background Research on outcomes associated with lifestyle interventions serving pediatric populations in urban settings, where a majority have severe obesity, is scarce. This study assessed whether participation in a lifestyle intervention improved body mass index (BMI) percentile, BMI z-score, blood pressure, and lipid levels for children and adolescents. Methods The Live Light Live Right program is a lifestyle intervention that uses medical assessment, nutritional education, access to physical fitness classes, and behavioral modification to improve health outcomes. Data was analyzed for 144 subjects aged 2-19 who participated for a minimum of 12 consecutive months between 2002 and 2016. McNemar tests were used to determine differences in the proportion of participants who moved from abnormal values at baseline to normal at follow-up for a given clinical measure. Paired sample t-tests assessed differences in blood pressure and lipid levels. Multiple linear regression assessed the change in blood pressure or lipid levels associated with improvement in BMI%95 and BMI z-score. Results The majority were female (62.5%), mean age was 9.6, and 71% were Black. At baseline, 70.1% had severe obesity, systolic hypertension was present in 44, and 13.9% had diastolic hypertension. One-third had abnormally low high-density lipoprotein (HDL) at baseline, 35% had elevated low-density lipoprotein (LDL), and 47% had abnormal total cholesterol (TC). The average difference in percentage points of BMI%95 at follow-up compared was − 3.0 (95% CI: − 5.0, − 1.1; p < 0.003). The mean difference in BMI z-score units at follow-up was − 0.15 (95% CI: − 0.2, − 0.1; p < 0.0001). Participants with systolic or diastolic hypertension had an average improvement in blood pressure of − 15.3 mmHg (p < 0.0001) and − 9.6 mmHg (p < 0.0001), respectively. There was a mean improvement of 4.4 mg/dL for participants with abnormal HDL (p < 0.001) and − 7.8 mg/dL for those with abnormal LDL at baseline (p = 0.036). For those with abnormal baseline TC, a one-unit improvement in BMI%95 was associated with a 0.61 mg/dL improvement in TC while holding constant age, contact hours, and months since enrollment (p = 0.043). Conclusions Participation in the program resulted in significant improvements in BMI percentile, BMI z-score, blood pressure, and lipid levels.